Development of Wolffia arrhiza as a Producer for Recombinant Human Granulocyte Colony-Stimulating Factor - Khvatkov, Pavel; Firsov, Alexsey; Shvedova, Anastasiya; Shaloiko, Lyubov; Kozlov, Oleg; Chernobrovkina, Mariya; Pushin, Alexander; Tarasenko, Irina; Chaban, Inna; Dolgov, Sergey (Frontiers in Chemistry, 2018)
To date, the expression of recombinant proteins in transgenic plants is becoming a powerful alternative to classical expression methods. Special efforts are directed to the development of contained cultivation systems based on cell culture or rhyzosecretion, which reliably prevents the heterologous DNA releasing into the environment. A promising object for the development of such systems is the tiny aquatic plant of wolffia (Wolffia arrhiza (L.) Horkel ex Wimm.), which can be used as a dipped culture in bioreactors. Herein we have expressed the human granulocyte colony-stimulating factor (hG-CSF) in nuclear-transformed wolffia. The nucleotide sequence of hG-CSF was optimized for expression in wolffia and cloned into the vector pCamGCSF downstream of double CaMV 35S promoter. Wolffia plants were successfully transformed and 34 independent transgenic lines with hG-CSF gene were obtained, PCR and Southern blot analysis confirmed the transgenic origin of these lines. Western blot analysis revealed accumulation of the target protein in 33 transgenic lines. Quantitative ELISA of protein extracts from these lines showed hG-CSF accumulation up to 35.5 mg/kg of wolffia raw weight (0.194% of total soluble protein). This relatively high yield holds promise for the development of wolffia-based expression system in strictly controlled format to produce various recombinant proteins.